Perspektif Hukum Islam Mengenai Hukum Shodaqoh - Suci Wulandari; Nazwa Febri Herviana; Rita Fitri Utami; Ahmad Zidan Al Arif; Muhammad Wisnu Haikal; Felixs Ade Santoso; Faishal Hasyim (Pusat Riset dan Inovasi Nasional, 2025)
Shodaqoh in the perspective of Islamic law is a noble act that contains social and spiritual values. In this study, shodaqoh is understood as a gift made sincerely to help others, either in the form of wealth, energy, or attention and without any reward. In the review of Islamic law, shodaqoh is classified into four categories, namely obligatory, sunnah, makruh, and haram. Obligatory shodaqoh applies under certain conditions, such as the obligation to pay zakat or provide assistance to those in dire need. Meanwhile, sunnah shodaqoh is recommended as a form of voluntary kindness, and makruh and haram shodaqoh are related to certain circumstances, such as bad intentions or non-halal sources of wealth. This research uses a normative method with a literature approach, which aims to examine the arguments from the Qur'an and Hadith as well as the views of scholars regarding the principles of shodaqoh management in accordance with Islamic law.